Narratives in public communication - Shen, Fuyuan; Edwards, Heidi Hatfield, 1966- (New York, NY : Routledge, 2023)
This volume explores the applications of narrative and storytelling in corporate, public health, and political communications, and its implications for those fields. Using diverse research methods including surveys, experiments, case studies, and content analyses, an international team of authors first explore conceptual and theoretical issues of narrative persuasion, then examine the impact and application of narratives in science communication, political advertising, corporate communication, and social movement before discussing the use of stories in community building, identity construction, and civic engagement. This timely volume will be of interest to academics, researchers, and graduate students who are interested in narratives and communications, within the areas of public relations, public communication, organizational communication, strategic communication, risk and crisis communication, and political communication.
Keywords: BUSINESS & ECONOMICS / Public Relations; Communication in organizations; Public relations; Risk communication; Communication in politics